Investigation of soil and plant nutrients in residential area in Parit Rasipan drainage system - Miswan, MS; Azman, MHA; Hamdan, R; Siddiqui, Z (2024)
Nutrient pollution pertains to elevated nitrogen, phosphorous, and potassium concentrations within aquatic systems. Nutrient pollution is the process by which excessive nutrients, primarily Nitrogen, Phosphorus and Potassium (NPK), are supplied to bodies of water and can act as fertiliser, causing excessive algal growth. This phenomenon is also known as eutrophication. Excessive nutrient levels can cause more severe issues, such as low dissolved oxygen levels in the water. The main objective of this study has been to evaluate the soil and plant nutrient content in the residential area of the Parit Rasipan drainage system. NPK levels were determined by collecting soil and plant samples at four specified sampling points within the study area, both during wet and dry days, using the APHA 4500 NORG-B and US EPA 6010B (ICP OES) methods. In addition to that, the pH, Dissolved Oxygen (DO), and temperature were recorded in situ. Water samples were also collected and analysed for specific parameters, including Total Nitrogen (TN), Total Phosphorus (TP), and Potassium (K). The analysis used a HACH DR6000 Spectrophotometer and Atomic Absorption Spectroscopy (AAS). The study findings indicate that the soil concentrations of TN (1660–2250 mg/kg), TP (100–360 mg/kg), and K (1020–1692 mg/kg) fall within the range of low to very high classifications. In the meantime, it is noteworthy that the concentrations of TN (4780–7870 mg/kg), TP (821–1640 mg/kg), and K (702–9160 mg/kg) in plants have been categorised as ranging from moderate to very high. In the context of water quality monitoring, the collected data indicates that the pH levels range from 3.16 to 3.22, the dissolved oxygen levels range from 0.95 to 0.98 mg/L, and the temperature ranges from 29.30˚C to 26.34˚C, observed during both wet and dry weather conditions. In summary, based on the analysis of the findings, it can be determined that the Parit Rasipan drainage system demonstrates a significant concentration of NPK elements under both wet and dry weather conditions, primarily due to residential activities occurring within the area.